Pemahaman Mahasiswa Tentang Saham Syariah Sebelum dan Sesudah Berdirinya Galeri Investasi Syariah BEI - Isnaini, Desi; Muslih, Cipta Isratul (Institut Agama Islam Bengkulu, 2020)
The purpose of this study is (1) to find out how students understand of Islamic Economics majors about Islamic stock investments before the establishment of the IDX Islamic Investment Gallery IAIN Bengkulu at the Faculty of Islamic Economics and Business. (2) to find out how students understand of Islamic Economics in the Islamic about stock investment department after the establishment of the Indonesia Stock Exchange Islamic Investment Gallery IAIN Bengkulu at the Faculty of Islamic data in the form is observation, interviews, and documentation. The results of this study is : (1) before enstabilistment GIS many students knows Islamic stocks is still limited to theory because there is no place of practice and educational tools to better understand about Islamic stock investment. (2) after the formation of GIS, students' understanding of sharia shares has increased compared to before the enstabilistment of GIS. Students have used existing support facilities.